Factor associated with delay in institutional delivery among mothers having under-2-year child in Badimalika Municipality, Bajura, Nepal: a cross-sectional study - Thapa, Arjun; Bham, Smriti (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Delay in institutional delivery refers to the time interval from the first onset of labor to the start of receiving the first health care. Delays in deciding to seek care, identifying and reaching medical facilities, and receiving adequate and appropriate treatment are three significant factors that contribute to maternal morbidity and mortality. This study aims to find the factors associated with institutional delays.Method: A cross-sectional study was conducted among mothers with children under 2 years old in Badimalika Municipality Bajura. Three wards (ward no. 7, 8 and 9) were selected purposively out of nine. The probability proportion size method was used to select study participants from each ward. A total of 230 mothers with under 2 children were selected. Face-to-face interviews were used to collect the data. Descriptive statistics and the chi-square tests were used to identify the factors associated with maternal delays.Result: The magnitudes of the first, second, and third maternal delays were 159(69.1%), 58(25.20%), and 60(26.10%), respectively. The first delay was significantly associated with unemployed women, birth preparedness, and mothers’ education level. Distance to a health facility and means of transportation were significantly associated with the second delay. The absence of obstetric drugs, a skilled health provider, and the need for referral were significantly associated with the third delay in institutional delivery.Conclusion: The magnitude of the first, second, and third maternal delays was high, which indicates that most mothers were not receiving institutional delivery services at the recommended time. Maternal socio-economic, accessibility, and healthcare system factors affected the three delays in this study